Hubungan Asupan Lemak Jenuh dengan Tekanan Darah pada Usia Dewasa Muda (20-40 Tahun) di Desa Prunggahan Kulon Kecamatan Semanding Kabupaten Tuban - Nabila Khoirunnisa; Dian Ayu Ainun Nafies (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Blood pressure is the result of the pressure exerted by blood on the walls of blood vessels. An increase in blood volume or blood vessel elasticity can result in an increase in blood pressure. High blood pressure is a condition in which systolic blood pressure exceeds 140 mmHg and diastolic blood pressure exceeds 90 mmHg, measured twice five minutes apart in a well-rested or calm state. There are several factors that affect blood pressure, one of which is saturated fat intake. This study aims to determine the relationship of saturated fat intake with blood pressure in young adults (20-40 years) in Prunggahan Kulon Village, Semanding District, Tuban Regency. Analytical research method with cross sectional approach. The population in this study were young adults in Prunggahan Kulon Village, Semanding District, Tuban Regency with a sample of 100 respondents, determined by probability sampling technique. Independent variable was saturated fat intake. The research analysis used Spearman correlation statistical test. The results showed that most respondents had excessive saturated fat intake (85%). Statistical test results with p-value = 0.000 (p < 0.05) showed there was a significant relationship between saturated fat intake and blood pressure. The conclusion of this study is that there is a tendency that the higher the intake containing saturated fat, the higher a person's blood pressure.